Análise documental e análise diplomática: perspectivas de interlocução de procedimentos - Nascimento, Lúcia Maria Barbosa do [UNESP] (2009)
The Documental Analysis, as an intrinsic process to the Information Organization in the Information Science domain, establishes theoretical-methodological parameters, of a descriptive nature, that make explicit the procedures of the analytical doing that lead to the identification of the document contents. Based on the assumption that this procedure has a technical support in the intersection of procedures with Diplomatics, the aim was to recover the genesis of the Diplomatic conception and to expose the disciplinary base of theoretical fundaments that establish its procedures for the analyses of the document form and content, as well as expose the intersection of procedures and also in which moment this can occur to contribute effectively to the analytical doing in the Librarianship area. The approach uses the exploratorytheoretical and descriptive-comparative analysis to expose the assumptions that are the basis of the intersection of procedures and how this is carried out. In order to make explicit the proposed auxiliary technique, the document book is used, by means of a comparative-analytical procedure. It was observed that the diplomatic procedure presents elements that make it possible to systematize the acting of the analyst through the description of the procedure intersection, what allowed highlighting the aiming in doing analysis before the structural systematization of the document characteristics. The result helps in the identification of concepts starting from the articulation elements of form-content that reveal the distinct statements of the book. Therefore, from the diplomatic conception of document analysis it is possible to insert in DA context the view of the analysis of document to text by using structural elements that make explicit and that contextualize the external and internal aspects of the document, by comparing the dimension of its content by means of the dimension of its form.